Deleuze and Guattari's philosophy of 'becoming-revolutionary' - Reyes, Raniel S. M. (Cambridge Scholars Publishing, 2020)
This book reconstructs Deleuze and Guattari's micropolitics toward a philosophy of 'becoming-revolutionary'. It provides novel ways to comprehend their political philosophy, through a critical engagement with Chantal Mouffe's theorization of radical democracy, Michael Hardt and Negri's diagnosis of Empire, Franco Berardi's analysis of semiocapitalism, the Philippine Party-List System Act, and the ASEAN Integration Project, to name a few. These initiatives aim to examine, expand, and challenge Deleuzo-Guattarian philosophy against the backdrop of various present-day predicaments and practices t.